H2O2-assisted detection of melamine using fluorescent probe based on corn cob carbon dots-Ionic Liquid-Silver nanoparticles. (1st March 2023) - Zheng, Yuxin; Hao, Jiawei; Arkin, Kamile; Bei, Yuyang; Ma, Xuesong; Shang, Qingkun; Che, Weilong
Graphical abstract: Highlights: A sustainable method for the accurate detection of melamine has been developed. Fluorescent probe was designed based on the interaction between H2 O2 and melamine. The carbon dots of the fluorescent probe are derived from food waste - corn cob. The detection limit for melamine is lower than the national standard method. The method was proven to accurately detect melamine in real dairy products. Abstract: In this work, a new sustainable melamine detection method was developed. Biomass-derived carbon dots (CDs) were successfully prepared by ionic liquid (1-Allyl-3-methylimidazolium chloride, IL) hydrothermal method using agricultural waste corn cob as the carbon source, and combined with silver nanoparticles (AgNPs) to construct fluorescent probe CDs@IL-AgNPs. The probe was characterized and the formation mechanism of the probe was discussed. The direct detection of H2 O2 and the indirect sensitive detection of melamine were realized. The detection limit of melamine was 0.94 μmol/L, which is far lower than the minimum allowable amount of melamine in milk powder (7.95 μmol/L). The high sensitivity and selectivity probe was used to detect melamine in commercial dairy products, and the recovery rate of standard addition was between 94 % and 110 %. This study provides valuable new application ideas for the detection of melamine in dairy products and the low-carbon and environmentally friendly treatment of agricultural waste.